Influence of spectroradiometric data collection methods under vegetation indexesin eucalipto - Schroder, Thomas; Zimmermann, Anna Paula Lora; Pereira, Rudiney Soares; Mortari Machado, Leonardo; Fleck, Marciane Danniela; Rocha, Najila Souza da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The spectroradiometry can detect the spectral response through direct contact with the target. Thus, the objective was to verify the influence of collect methods, Eucalyptus grandis leaves in vegetation indices as collect position in the canopy, Cardinal point and season. Data were collected at two different stands on two dominant trees each. 15 leaves were collected at each position and in each direction, plus a sample of the same size at the center. The material was analyzed with FieldSpec®3 spectroradiometer and the spectral response of each orientation and position wasgiven by the average spectral reading of the leaves. 60 different vegetation indexes according to the literature were analyzed. To evaluate the effect of season on the indices samples were taken in four seasons. Mixed models were used to analyze the influence in factors (position and station) and their interaction. Data were considered nested in each orientation, within each tree and each area. Statistical analysis was performed using R software with nlme package. Vegetation indexesanalyzed six are dependent of the position, orientation andstation